High‐resolution geospatial surveying techniques provide new insights into rock‐art landscapes at Shuwaymis, Saudi Arabia. (May 2014) - Jennings, Richard; Parton, Ash; Groucutt, Huw S.; Clark‐Balzan, Laine; Breeze, Paul; Drake, Nick A.; Alsharekh, Abdullah; Petraglia, Michael D.
<x xml:space="preserve">Abstract</x> Many parts of the Arabian Peninsula contain rock art that has received minimal archaeological attention or has not yet been thoroughly surveyed. In 2001 an extensive rock‐art complex called Shuwaymis, Ha'il Province, Saudi Arabia was brought to the attention of the Saudi General Commission for Tourism and Antiquities. This paper sets out the results of the first high‐resolution geospatial mapping and recording of rock art at this remote site. The research saw the innovative use of a differential GPS to record rock‐art panels to within 5 mm of accuracy at the site of Shuwaymis‐2, the first time that such technology has been used to record rock art in the Arabian Peninsula. With such technology it was possible to show which of eighty‐three late prehistoric rock‐art panels surveyed were in their original position and which had fallen, and to demonstrate that there was spatial homogeneity of rock‐art styles and composition across the site. The mapping recorded multiple panels of cattle, ibex, equid, large cat and other animals. The depictions of lions and cattle in particular indicate that the rock art must have been engraved no later than the early Holocene humid phase (c.10–6 ka BP).